2022
DOI: 10.2147/ijgm.s379642
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Sensitivity of Bacterial Colonization on the Tip of Non-Tunneled Temporary Hemodialysis Catheters: Results of a Tertiary Hospital in Somalia

Abstract: Bacterial colonization on the tip of non-tunneled temporary hemodialysis catheters (NTHCs) and associated catheterrelated infections (CRI) is a common complication in hemodialysis (HD) patients. In this study, we aimed to investigate the pattern of bacterial colonization formed on the tip of non-tunneled temporary hemodialysis catheters and their antibiotic sensitivity. Methods: This retrospective analysis was performed in the HD unit of an Education and Research Hospital that follows up a universe of approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
(24 reference statements)
0
6
0
4
Order By: Relevance
“…23 According to our study, Staphylococcus aureus and Staphylococcus epidermidis are the most common microorganisms in patients with CVCrelated bacteremia, supported by the results of other studies. 8,[14][15][16][23][24][25] Our study shows that a prior CVC infection is an independent predictor for the development of CVC-related bacteremia in children undergoing h e m o d i a l y s i s . P r e v i o u s s t u d i e s , a s t h e one carried out by Weldetensae et al in a population with CVC, where 93.9% had a nontunneled catheter, demonstrated that a prior infection increased 12 times the probability of developing a subsequent infection.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…23 According to our study, Staphylococcus aureus and Staphylococcus epidermidis are the most common microorganisms in patients with CVCrelated bacteremia, supported by the results of other studies. 8,[14][15][16][23][24][25] Our study shows that a prior CVC infection is an independent predictor for the development of CVC-related bacteremia in children undergoing h e m o d i a l y s i s . P r e v i o u s s t u d i e s , a s t h e one carried out by Weldetensae et al in a population with CVC, where 93.9% had a nontunneled catheter, demonstrated that a prior infection increased 12 times the probability of developing a subsequent infection.…”
Section: Discussionmentioning
confidence: 98%
“…1,2 According to the different series, the incidence of bacteriemia a s s o c i a t e d w i t h n o n -t u n n e l e d C V C s i s 3.25-10.8 events per 1000 catheter-days, while that of tunneled CVCs is 0.55-5.5. [8][9][10][11][12][13][14] The most common microorganisms are Staphylococcus aureus or epidermidis. [8][9][10][11][12][13][14] Among adults, the risk factors for infection include a prolonged CVC dwell time, decrease in hemoglobin and albumin serum levels, prior catheter-related bacteremia, diabetes, iron overload, nasal colonization with Staphylococcus aureus, malnutrition, and advanced age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, in contrary to our ascertained microbial pattern, many studies reported Gram-positive organisms were implicated for majority of the CRBSIs. [11][12][13] Knowing the antibiotics sensitivity pattern of bacterial isolate or growth in HD unit is significant to select the suitable empiric antibiotics. In the current study, more than half of the S. aureus isolates were cloxacillin resistant, in line with this study, Fram and his associates reported that 38.5% of their S. aureus isolates were oxacillin resistant.…”
mentioning
confidence: 99%
“…This is similar to the result found by Abdinafi et al which was done in a similar setup in Somalia. 12 Regarding Gram-negative pathogens, they displayed 90% sensitivity to Imipenem, 87% to Amikacin, and 63.3% to…”
mentioning
confidence: 99%